Interaksi antara Proyektil dan Komposit Polimer diperkuat Butiran Silikon Karbid (SiCp) dan Serat Karbon pada Pengujian Balistik - Simon Anakottapary, Daud; Tirta Nindhia, Tjokorda Gde (Jurnal Energi Dan Manufaktur; Vol 4, No.2 Oktober 2010, 2012)
With increasing the security treat and terrorisms that involving the use of firearm and to optimize the security thenmaximum protection for he safety of the security guards, armies, and polices should be put in consideration. In order toconduct their duties properly and to protect their safety, the security guard should be completed with bulletproof body armor.Since the price of commercial bulletproof body armors is very expensive that only special force is possible to have it. It is thepurpose of this research to develop material for bulletproof body armor with reasonable price but having good performancethat can be used by security guard. In this research the SiCp was pressed in order to have a diameter surface in the 11.5cmand high 1 cm mould. Afterward the mixture of polyester and carbon fiber was poured in to the mold until reach 1 cmthickness. The natural cooling was done naturally for about 24 hours with addition of catalyst to solidify the composite. Theballistic test performance will be conducted with cooperation with the institution that has authority for this activity, and theresult will be analyzed and reported.
Keywords: bulletproof body armor, composite, polyester, silicon carbide, carbon fiber